(untitled) (Bangladesh Critical Care Journal, 2023)
Objective: To assess the efficacy of vitamin C as an adjunct to Selective Serotonin Reuptake Inhibitors (SSRIs) in treating OCD patients. Design: Single-blind randomized controlled trial. Study eligibility: Randomly selected 96 OCD patients diagnosed by the psychiatric consultants following the DSM-5 criteria of both sexes aged 18 years and above were initially enrolled; finally, 83completed the study. The study was conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU) in Dhaka, Bangladesh, from March 2018 to February 2019. Interventions: After obtaining written informed consent, participants were randomly divided into group A (control group) and group B (intervention group). A baseline recording of the body’s endogenous antioxidant markers (plasma vitamin C and erythrocyte glutathione levels), oxidative stress marker (plasma malondialdehyde), and Yale-Brown score of OCD by Yale-Brown Obsessive-Compulsive Scale(Y-BOCS) were measured in both groups. The control group (n=40) received oral SSRIs daily for eight weeks, while the intervention group (n=56) received the SSRIs plus oral vitamin C (500 mg twelve hourly) daily for the same duration. The biochemical parameters and the Y-BOCS score of OCD of both groups were obtained after eight weeks, and the result was analyzed and compared. Main outcome measures: The outcomes were levels of plasma vitamin C, erythrocyte (RBC) glutathione and plasma malondialdehyde, and the Yale-Brown Obsessive-Compulsive Scale (Y-BOCS). Result: Baseline recordings suggest significantly (p<0.05) lower levels of plasma vitamin C and RBC glutathione concentrations and non-significant (p>0.05) higher levels of plasma MDA concentrations in both groups. After eight weeks of intervention with vitamin C plus SSRIs, plasma vitamin C and RBC glutathione levels were significantly (p<0.001) increased more in the intervention group compared to the control group (97.26% vs 44.44% and 57% vs 44.16%, respectively). On the other hand, plasma MDA concentrations and the mean Y-BOCS score were reduced more in the intervention group compared to their counterpart (48.15% vs 37.74% and 29.69% vs 21.74%; p<0.001). Conclusion: The result showed that vitamin C adjunct to SSRIs in OCD patients had significantly improved vitamin C and RBC glutathione concentrations, while the plasma MDA level and the Y-BOCS score were decreased in the intervention group. Treatment with vitamin C leads to a more significant improvement in OCD symptoms. Trial registration: Registered with Clinical Trials. Gov (NCT03754647). Bangladesh Crit Care J March 2023; 11 (1): 24-30